Opportunities and Challenges in Enhancing Students' Science Literacy - Aqilah, Siti; Pursitasari*, Indarini Dwi; Permana, Irvan; Ardianto, Didit; Rachman, Indriyani (Universitas Syiah Kuala, 2025)
Science literacy is a skill that students need to have to face the challenges of the 21st century. One aspect that can improve science literacy is the use of teaching materials. The purpose of the study was to analyze the opportunities and challenges of improving students' science literacy using teaching materials. The research method used was a systematic literature review with a preferred reporting items for systematic reviews and meta-analysis (PRISMA) flowchart. The results showed that opportunities to improve science literacy are done through various ways including the use of teaching materials, in-depth review of books, and the use of technology. However, learning that involves science activities is still few and more conceptual. In addition, the teaching materials used only contain subject matter and examples of problems and solutions, without encouraging students to find learning concepts. The conclusion obtained is that teaching materials that can be used to improve science literacy include comics, multimedia, books, e-modules, worksheets, and mobile-based learning media.